Genetic variability and trait association in chickpea (Cicer arietinum L.) genotypes at seedling stage - Qurban Ali, Muhammad Ahsan and Jehanzeb Farooq (Electronic Journal of Plant Breeding, 2010)
Eighty elite lines including ten standard varieties of chickpea were evaluated for various seedling parameters. Positive andsignificant genotypic and phenotypic correlations were found for different parameters like seedling length, root length,root/shoot ratio, seedling biomass, leaf length, leaf width and leaf area while root length was positively and significantlycorrelated with other parameters. Root/shoot ratio was positively and significantly correlated with all parameters. Seedlingbiomass had positive and significant genotypic and phenotypic correlations with all the parameters. Leaf length, leaf widthand leaf area also had positive and significant correlation among each other and with other parameters. The estimates of theheritability were high for seedling length, root length, moderate for the root/shoot ratio, seedling biomass and primary leafarea and slightly low for the primary leaf length and leaf width. Higher estimates of heritability and positive correlationcoefficients for seedling length, root length, seedling biomass, leaf length, leaf width and leaf area suggest that selection ofelite genotypes at seedling level might be effective for further breeding programme.